Development of cycle-to-cycle variation of the tumble flow motion in a cylinder of a spark ignition internal combustion engine with Miller cycle. (May 2021) - Matsuda, Masayoshi; Yokomori, Takeshi; Shimura, Masayasu; Minamoto, Yuki; Tanahashi, Mamoru; Iida, Norimasa
Reducing the cycle-to-cycle variation in an engine is a key to expanding the operational limits of high-efficiency engines such as lean-burn engines. The cycle-to-cycle variation of the engine output is caused by unstable combustion and is especially induced by the cycle-to-cycle variation of the in-cylinder flow. This investigation aims to clarify how the cycle-to-cycle variation of in-cylinder flow develops during intake and compression strokes. To achieve this aim, 12 kHz time-resolved particle image velocimetry measurements were conducted on the symmetrical vertical plane in a four-valve, four-stroke optically accessible engine. This study focuses on the relationship between the flow at the plug position at the ignition timing and the flow distribution in the intake and compression stroke. Correlation map analysis reveals this relationship, and some flow distributions are extracted. The fluctuations in the flow distribution induce the cycle-to-cycle variation of the flow direction at the plug position at the ignition timing, the position of the stagnation plane between the intake flow from the intake valves and the upper side of the tumble vortex, the strength of the blowback flow into the intake port generated by the Miller cycle, and the position of the tumble vortex in the late compression stroke. The flow distributions extracted by the correlation map analysis clearly change between cycles. These results also suggest that correlation map analysis is an effective way to elucidate the factors that induce the cycle-to-cycle variation of the in-cylinder flow.